2018
DOI: 10.1109/tnsre.2017.2731261
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Class Tactile Brain–Computer Interface Based on Stimulus-Induced Oscillatory Dynamics

Abstract: Abstract-We proposed a multi-class tactile brain-computer interface that utilizes stimulus-induced oscillatory dynamics. It was hypothesized that somatosensory attention can modulate tactile induced oscillation changes, which can decode different sensation attention tasks. Subjects performed four tactile attention tasks, prompted by cues presented in random order and while both wrists were simultaneously stimulated: 1) selective sensation on left hand (SS-L), 2) selective sensation on right hand (SS-R), 3) bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 50 publications
4
29
0
Order By: Relevance
“…In six out of seven experimental sets [18], [19], [23], [41], [53]- [55] (as seen in table 1), EEG signals were recorded using a SynAmps2 system (Neuroscan, U.S.A.). A 64-channel quick-cap was used to collect 62-channel EEG signals, and the electrodes were placed according to the extended 10/20 system.…”
Section: B Eegmentioning
confidence: 99%
See 2 more Smart Citations
“…In six out of seven experimental sets [18], [19], [23], [41], [53]- [55] (as seen in table 1), EEG signals were recorded using a SynAmps2 system (Neuroscan, U.S.A.). A 64-channel quick-cap was used to collect 62-channel EEG signals, and the electrodes were placed according to the extended 10/20 system.…”
Section: B Eegmentioning
confidence: 99%
“…Twenty subjects participated in the second SS protocol [41], with the g.Tec system. During the SS task period, sustained vibrotactile stimuli were simultaneously applied to both wrists.…”
Section: Experimental Protocols For Tactile Selective Sensationmentioning
confidence: 99%
See 1 more Smart Citation
“…This system achieved a mean accuracy of 72% in 11 subjects, when selecting between two targets. By comparison, we have shown that BCI based on tactile selective sensation has largely increased tactile BCI performance by approximately 10%, and this tactile BCI modality based on SS substantially outperformed previous tactile BCI systems, making it potentially applicable to a larger number of users [36], [37]. The ERD/ERS oscillatory response and SSSEP response provide complementary information of the somatosensory input processing.…”
Section: Discussionmentioning
confidence: 92%
“…Brain oscillatory dynamics, as quantified by event related desynchronization/synchronization (ERD/ERS) [31], [32], are not only correlated with real or imagined movement, but also with external sensory stimulation processing [33], [34]. We have previously shown that tactile-induced oscillatory dynamics provide a reliable brain signal modality for a tactile BCI [35]- [37]. Furthermore, this oscillatory activity is not only correlated with real tactile sensation, but also with imagined sensation [15].…”
Section: Introductionmentioning
confidence: 99%